Three-part differential of unlabeled leukocytes with a compact lens-free imaging flow cytometer. Issue 4 (24th December 2014) - Vercruysse, Dries; Dusa, Alexandra; Stahl, Richard; Vanmeerbeeck, Geert; de Wijs, Koen; Liu, Chengxun; Prodanov, Dimiter; Peumans, Peter; Lagae, Liesbet
Abstract : We assemble a compact lens-free in-line holographic microscope, employ it to image blood cells flowing in a microfluidic chip and perform a three-part leukocyte differential based on the acquired images. Abstract : A compelling clinical need exists for inexpensive, portable haematology analyzers that can be utilized at the point-of-care in emergency settings or in resource-limited settings. Development of a label-free, microfluidic blood analysis platform is the first step towards such a miniaturized, cost-effective system. Here we assemble a compact lens-free in-line holographic microscope and employ it to image blood cells flowing in a microfluidic chip, using a high-speed camera and stroboscopic illumination. Numerical reconstruction of the captured holograms allows classification of unlabeled leukocytes into three main subtypes: lymphocytes, monocytes and granulocytes. A scale-space recognition analysis to evaluate cellular size and internal complexity is also developed and used to build a 3-part leukocyte differential. The lens-free image-based classification is compared to the 3-part white blood cell differential generated by using a conventional analyzer on the same blood sample and is found to be in good agreement with it.